Optimasi Usaha Pengolahan Limbah Plastik Dengan Pendekatan Simulasi - Syaifuddin Yana Syaifuddin Yana (Jurnal Serambi Engineering, 2016)
This researchintent to analyze the optimization of waste plastics processing industry into a plastic chip products. The plastic waste processing using various types of plastic waste materials obtained through various sources such as scavenger and waste collectors which are they are living around the community, and others source. This study uses a model of maximizing profits based on assumptions by using a simulation of plastic waste processing plan within a year to consider following the prevailing price in the market within the last few years. In addition, to assess the feasibility of processing waste plastics by using parameters such investments Benefit Cost Ratio (BCR), Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP) and Profitability Index (PI). The results of the processing of the data obtained shows that optimizing the processing of plastic waste into plastic count based on the simulation of 3 (three) variables X1, X2 and X3 is the condition where i = 18% where X1 = 100% and X2 and X3 = 0%, with gains in the amount of USD 127 604 565.